2015
DOI: 10.1186/s13104-015-1460-x
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon presentation of Kikuchi Fujimoto disease: a case report with literature review

Abstract: BackgroundKikuchi–Fujimoto disease is so named because Kikuchi and Fujimoto were the first scientists to describe it in Japan in 1972. Although the disease has been reported from all over the world and more so from Asia, it is rare. To date only eight cases have been reported from Nepal. Cervical lymphadenopathy, fever and raised Erythrocyte Sedimentation Rate are usual presenting features of this disease. We describe a case which presented with thrombocytopenia and axillary lymphadenopathy in addition to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Kwon et al ( 32 ) reported that the mean maximum diameter of the affected cervical LNs was 1.62 cm in 1,196 KFD LNs from 96 patients ( 32 ). Furthermore, KFD LNs may be >2.5 cm ( 4 , 43 ). KFD LNs may thus resemble metastatic lesions, based on palpation, though clinical palpation of the neck has been reported to be unreliable ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kwon et al ( 32 ) reported that the mean maximum diameter of the affected cervical LNs was 1.62 cm in 1,196 KFD LNs from 96 patients ( 32 ). Furthermore, KFD LNs may be >2.5 cm ( 4 , 43 ). KFD LNs may thus resemble metastatic lesions, based on palpation, though clinical palpation of the neck has been reported to be unreliable ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Youk et al ( 48 ) also indicated that KFD tended to be misdiagnosed as malignancy on the basis of US findings. Furthermore, FDG uptake in FDG-PET/CT is not specific for cancer ( 4 , 47 ). Regarding time to recurrence, KFD typically recurs within 1 year of its initial resolution ( 5 , 49 ), while LN metastasis also occurs within 1 year ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kikuchi-Fujimoto Disease (KFD) is the most common cause of histiocytic necrotizing lymphadenitis (non-granulomatous inflammation and necrosis of the lymph node), followed by systemic lupus erythematosus -SLE and acute Epstein Barr virus -EBV lymphadenitis [1,2]. It is a rare disease that was described for the first time in Japan, independently by Kikuchi and Fujimoto, in 1972 [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Kikuchi-Fujimoto Disease (KFD) is the most common cause of histiocytic necrotizing lymphadenitis (non-granulomatous inflammation and necrosis of the lymph node), followed by systemic lupus erythematosus -SLE and acute Epstein Barr virus -EBV lymphadenitis [1,2]. It is a rare disease that was described for the first time in Japan, independently by Kikuchi and Fujimoto, in 1972 [1,2]. It is a benign and self-limiting condition characterized by regional lymphadenopathy (usually posterior cervical, in 60-90% of cases) associated with fever, and other signs and symptoms such as cutaneous lesions, arthritis, fatigue and hepatosplenomegaly [3,4].…”
Section: Introductionmentioning
confidence: 99%